Penerapan Metode Al-Miftah lil ‘Ulum untuk Meningkatkan Kemampuan Baca Kitab Kuning: Studi Kasus di Pondok pesantren Miftahul Ulum Pandanwangi - Muhammad Ainur Roziqin; Hasbunallah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Starting from the main boarding school, which in this case is used and tried by the Sidogiri Pasuruan Islamic boarding school, many other boarding schools also use the Al-Miftah lil Ulum method, including the Islamic boarding school that the author will research, namely the Miftahul Ulum Pandanwangi Islamic boarding school which has applied the Al-Miftah lil Ulum Method since the beginning of 2018. During this period, at least it can be analyzed from the implementation and learning process. This Sidogiri cottage can be implemented well and the maximum is with the same time, producing different qualities; quality equals shorter time, better quality with a short period of time. However, the learning effectiveness of a method applied in an institution will show significant differences in results with other institutions that also apply the method. This is certainly influenced by several things, both in terms of process, inhibiting and supporting factors, as well as other factors such as the environment and the like. The focus and objectives of this study are 1) Learning planning of the Al-Miftah lil Ulum method in improving the competence of reading the yellow book at the Miftahul Ulum Pandanwangi Islamic Boarding School, 2) Organizing the learning of the Al-Miftah lil Ulum method in improving the competence of reading the yellow book at the Miftahul Ulum Pandanwangi Islamic Boarding School, 3) The implementation of the Al-Miftah lil "Ulum method in improving the competence of reading the yellow book at the Miftahul Ulum Pandanwangi Islamic Boarding School,  4) Evaluation of the Al-Miftah lil Ulum method in improving the competence of reading the yellow book at the Miftahul Ulum Pandanwangi Islamic Boarding School. This study uses a descriptive qualitative approach with a case study research type. The techniques used in data mining are interviews, field notes, images, photos, video recordings and so on. Based on the results of the research, the following conclusions can be obtained: 1) Learning planning of the Al-Miftah lil Ulum method Holding a meeting with a number of asatids at the Miftahul Ulum Pandanwangi Islamic Boarding School 2) Organizing the learning of the Al-Miftah lil Ulum method Individual approach, Each class has a companion teacher who has gone through special training, so that students can focus on one material and get an in-depth explanation without being disturbed 3) Implementation learning the Al-Miftah lil Ulum method Gradual approach: The material is presented in four volumes, starting from the most basic to a more complex level 4) The evaluation of learning the Al-Miftah lil Ulum method is multi-stage, Flexible, Comprehensive, and has clear goals.